2021
DOI: 10.3390/foods10071512
|View full text |Cite
|
Sign up to set email alerts
|

Active Carboxymethylcellulose-Based Edible Films: Influence of Free and Encapsulated Curcumin on Films’ Properties

Abstract: Carboxymethylcellulose (CMC)-based films can act as a protective barrier in food surfaces and a carrier of bioactive compounds, such as curcumin. However, incorporating curcumin in hydrophilic matrixes can be a challenge, and new strategies need to be explored. In this work, CMC-based films containing free curcumin and curcumin-loaded nanohydrogels (composed of lactoferrin and glycomacropeptide) were produced and characterized. The incorporation of curcumin-loaded nanohydrogels showed a significant decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 34 publications
0
4
0
5
Order By: Relevance
“…Another example of a film with additives, according to Bourbon et al [116], is carboxymethylcellulose-based films, which can act as a protective barrier on food surfaces, serving as carriers of bioactive compounds such as curcumin. This study also showed that protein-based nanohydrogels could be a good strategy for incorporating curcumin into edible films, highlighting their potential for use in food applications, mainly due to their antioxidant and antimicrobial activity, which could extend the shelf life of foods.…”
Section: Polymeric Filmsmentioning
confidence: 99%
“…Another example of a film with additives, according to Bourbon et al [116], is carboxymethylcellulose-based films, which can act as a protective barrier on food surfaces, serving as carriers of bioactive compounds such as curcumin. This study also showed that protein-based nanohydrogels could be a good strategy for incorporating curcumin into edible films, highlighting their potential for use in food applications, mainly due to their antioxidant and antimicrobial activity, which could extend the shelf life of foods.…”
Section: Polymeric Filmsmentioning
confidence: 99%
“…Penentuan faktor terdiri dari tiga variabel bebas, yaitu konsentrasi CMC, lilin lebah, dan gliserol (Tabel 1). Penentuan faktor diperoleh berdasarkan kajian penelitian Bourbon et al (2021), Safitri et al (2020), dan Sari et al (2008) yang mendapatkan konsentrasi CMC 2% (b/v), lilin lebah 2% (b/v), dan gliserol terbaik yaitu 1-2% (v/v), serta dilakukan penelitian pendahuluan untuk mendapatkan ketiga konsentrasi terbaik dalam penentuan batas atas dan bawah dengan melihat respon ketebalan dan heat sealability. Kolangkaling sebanyak 10 g dan akuades sebanyak 100 mL ditetapkan sebagai variabel tetap.…”
Section: Penentuan Faktor Respon Terpilih Dan Kepentingan Pemilihan K...unclassified
“…It is a common ingredient in food gels, such as processed meat products, dry pet foods, yoghurt, beverages, ice cream and dessert. In addition to these, CMC can provide control to the viscosity of film-forming solution, and protective barrier when used in food packaging film applications [44].…”
Section: Etherificationmentioning
confidence: 99%